Institutionalised, Parentless, and Racialised as Other: Understanding the Formation of a Racialised Self for Women of African-Irish Descent who grew up in the Irish Industrial School System - Mullen, Mary Philomena (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Sociology, 2021)
This research investigated the identity(ies) construction of 15 women of mixed African-Irish descent, with white Irish mothers and African fathers, who as children grew up in the Irish institutional care system in the 1950s-1980s. The conceptual perspective of critical mixed race studies led me to conduct qualitative research. My experience of growing up in an industrial school led to the application of autoethnographic principles. Semi-structured interviews were used and were thematically analysed. Data analysis suggested four themes: 1) mixed race experience and racialised discourses; 2) social relations and social racialisation; 3) life in the institution; and 4) life after the institution. There are four key findings which emerge. First, many of the participants experienced the deleterious impact of being racialised in the institutions as children. Secondly, the denial of and/or failure to create a relationship with their white mothers and black fathers played a significant part in their (re)construction of individualised identities made up of the constituent elements of racialisation and institutionalisation. Thirdly, many expressed a deep desire to discover more about their Irish mothers and African fathers with a view to establishing a potential connection to this imagined presence. Finally, the combined effects of being parentless, institutionalised and Othered resulted in a subjective (re)construction of a racial self that is realistic and accommodating of the social reality of how they are perceived in a racial state. The research theorises that this was a fundamental factor in how they became racialised inside the institutions before they ever encountered the wider community where they continued to be racialised as other and perceived as not belonging. For some, this led to them leaving Ireland almost on discharge from the institutions to forge an identity in Britain, Europe and the US. For most, however, their identity(ies) was framed, along with their white fellow inmates, within a collective identity of being an incarcerated industrial school child. Socialised as Irish but racialised as Other, the treatment of the mixed race children in the industrial school complex was based on the racialised abuse received at the hands of the religious orders, the staff in whose care they were placed, and the other white children. This is expressed through the individual narratives of the people who took part. The research asserts that mixed race children in institutional care were singled out for a particular form of abuse. Some of the participants have unproblematic memories of their times in the industrial schools. Others, however, speak of being denied access to mother, father, and siblings; of having to work, cleaning and caring for other children (while being little more than small children themselves); of not going to school but instead being put to work either within the institution or being sent out to do adult work in laundries or as domestic workers; of being fostered to families on weekends and in school holidays where they suffered emotional, physical, racial and even sexual abuse before being summarily returned to the industrial school; and through a corruption of care, suffering harsh, demeaning and damaging treatment within the total institutional context.
APPROVED
Keywords: Institutionalised; Racialised; Mixed-Race Irish; Industrial Schools; Institutional Care; Gender and Race; Irish identities; African-Irish